Keefektifan Projek Penguatan Profil Pelajar Pancaasila dan Wawasan Edupreneurship Terhadap Kreativitas Peserta Didik - Chandrasari, Tri Ratna; Purnamasari, Iin; Handayani, Arri (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Creativity for students is one of the foundations for children to be able to solve problems, think out of the box, and explore something new. All of that can be capital for children's success, whatever field they choose in the future. The low creativity of students at SD Negeri Mas can be seen from the results of the 2023 Education Quality Report which concluded that in students who are unable to link concepts, come up with ideas or concepts related to the material they have received, so that they cannot develop independent students in learning and creative in dealing with a problem according to the objectives of learning. This study aims to determine the effectiveness of the Pancasila Student Profile Strengthening Project (P5) and edupreneurship insights on student creativity at SD Negeri Tanjung Mas, Semarang City. This study uses a descriptive quantitative method. Data collection techniques are carried out by surveys in the form of questionnaires, observations, and documentation. The questionnaire and observation guidelines are compiled using the creativity theory framework. The results of the study indicate that the Pancasila Student Profile Strengthening Project (P5) and edupreneurship insight partially and together have a significant positive effect on student creativity. In addition, the results of the study also show that the Pancasila Student Profile Strengthening Project (P5) and edupreneurship insight are effective in increasing student creativity. As educators, we must be able to arouse student creativity which is not only influenced by the quality of learning but other factors can also affect student creativity.